Operations for portal hypertension due to extrahepatic obstruction: results and 10 year follow up. Issue 6606 (31st October 1987) - Pande, G K; Reddy, V M; Kar, P; Sahni, P; Berry, M; Tandon, B N; Nundy, S
Abstract : Between 1976 and 1984, 136 patients with portal hypertension due to extrahepatic obstruction were operated on. Twenty two patients had emergency and 114 elective operations. The operative mortality was 9% and 1%, respectively. Altogether 117 patients (86%) were followed up for from two to 10 years: 17 rebled, none developed encephalopathy or sepsis after splenectomy, and 90% and 75% were alive at five and 10 years respectively. Unlike endoscopic sclerotherapy and treatment with propranolol, operative treatment of variceal bleeding can usually be completed during one admission and carries a low mortality and a fairly low morbidity. Operation seems to be the best form of treatment for poor patients living far from medical facilities in developing countries and may be the treatment of choice in developed countries as well.